Fostering students’ Multimodal Communicative Competence through genre-based multimodal text analysis - Fuad Abdullah; Arini Nurul Hidayati; Agis Andriani; Dea Silvani; Ruslan Ruslan; Soni T. Tandiana; Nina Lisnawati (Studies in English Language and Education, 2022)
The multiplicity of semiotic resources employed in communication, the rapid advancement of information, communication, and technology (ICT), and burgeoning interdisciplinary research into multimodality have led to a paradigmatic shift from a mono-modal to the multimodal perspective of communication. Conversely, actualising multimodal concepts in teaching and learning practises remains underexplored, notably in developing the students’ multimodal communicative competence (MCC). For this reason, this study endeavoured to probe genre-based multimodal text analysis in fostering the students’ MCC. Grounded on Action Research (AR), the present study facilitated students to cultivate their MCC through the activities of Genre-based multimodal text analysis (hereafter, GBMTA). Practically speaking, students performed the analysing practises in the course at an English Education Department of a state university in Tasikmalaya, West Java, Indonesia, namely Grammar in Multimodal Discourse (GiMD. Four Indonesian EFL students were recruited as the participants. The data were collected through semi-structured interviews and analysed with thematic analysis. The findings showed that the students could: (1) build their knowledge on multimodality, (2) engage with theoretical and practical learning activities, (3) assign analytical and reflective task-based learning activities, and (4) provide constructive feedback about their learning performances, and (5) raise awareness of the contributions of multimodality to prospective English teachers’ competences. The main implication of this study is the promotion of increased awareness of deploying multimodal aspects to English language teaching, learning, and investigative practises to attain optimum MCC.